Concurrent dual‐band digital predistortion method for wideband power amplifier with large carrier spacing two‐carrier signal. Issue 3 (March 2014) - Xiang, Haixia; Yu, Cuiping; Gao, Jinchun; Li, Shulan; Wu, Yongle; Su, Ming; Liu, Yuanan
ABSTRACT A concurrent dual‐band three‐layered biased memory polynomial (DB‐TLBMP) model is proposed for the linearization of wideband power amplifiers driven by large carrier spacing two‐carrier signals. The DB‐TLBMP model is derived by extending the TLBMP model to the concurrent dual‐band mode, and the least square algorithm is used for coefficients extraction of each layer. Using a two‐carrier wideband code division multiple access signal with 40‐MHz carrier spacing at 2.65 GHz, whose peak‐to‐average power ratio is 7.74 dB, the adjacent channel leakage ratios (ACLRs) improvement of more than 17 dBc are achieved to give the ACLRs below −50 dBc at the offset of ±5 MHz and an average output power of 37 dBm. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:594–597, 2014